2017
DOI: 10.1016/j.apsb.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Anemone medicinal plants: ethnopharmacology, phytochemistry and biology

Abstract: The Ranunculaceae genus Anemone (order Ranunculales), comprising more than 150 species, mostly herbs, has long been used in folk medicine and worldwide ethnomedicine. Various medicinal compounds have been found in Anemone plants, especially triterpenoid saponins, some of which have shown anti-cancer activities. Some Anemone compounds and extracts display immunomodulatory, anti-inflammatory, antioxidant, and antimicrobial activities. More than 50 species have ethnopharmacological uses, which provide clues for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 42 publications
(57 reference statements)
2
35
0
7
Order By: Relevance
“…The rhizome of Anemone raddeana Regel is used in Chinese conventional therapies to cure rheumatism, arthritis, neuralgia, paralysis and other diseases [30][31][32]. The anemone herb contains oleanane triterpenoid saponins accompanied by lactones, alkaloids, saccharide, triterpenoids and fats [33,34]. In the past few years, various bioactive saponins compounds have been extracted from this plant, including RA, which has gained importance due to its anti-inflammatory, analgesic, and antitumor activities [33].…”
Section: Introductionmentioning
confidence: 99%
“…The rhizome of Anemone raddeana Regel is used in Chinese conventional therapies to cure rheumatism, arthritis, neuralgia, paralysis and other diseases [30][31][32]. The anemone herb contains oleanane triterpenoid saponins accompanied by lactones, alkaloids, saccharide, triterpenoids and fats [33,34]. In the past few years, various bioactive saponins compounds have been extracted from this plant, including RA, which has gained importance due to its anti-inflammatory, analgesic, and antitumor activities [33].…”
Section: Introductionmentioning
confidence: 99%
“…The plant is considered unofficinal, though it is widely used in folk medicine as an antitumor, sedative, bactericidal, antimicrobial, antifungal, anti-inflammatory, spasmolytic diaphoretic, expectorant, and diuretic drug [5][6][7][8][9][10][11]. The major biologically active substances in Anemone nemorosa are: alkaloids, glycosides (proto-anemonin, anemonin, ranunculin, some types of saponins, tannins), vitamin C, resins, organic acids (chelidonic acid), coumarins, flavonoids, and γ-Linolenic acid [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…18 Preclinical studies have indicated the antitumour activity of RA against gastric cancer, colorectal cancer, breast cancer, liver cancer, choriocarcinoma, glioblastoma and osteosarcoma. 18 Preclinical studies have indicated the antitumour activity of RA against gastric cancer, colorectal cancer, breast cancer, liver cancer, choriocarcinoma, glioblastoma and osteosarcoma.…”
mentioning
confidence: 99%
“…Raddeanin A (RA) is an oleanane-type triterpenoid saponin extracted from the root of Anemone raddeana Regel, a traditional Chinese medicinal herb used to treat rheumatism and arthritis in ancient China. 18 Preclinical studies have indicated the antitumour activity of RA against gastric cancer, colorectal cancer, breast cancer, liver cancer, choriocarcinoma, glioblastoma and osteosarcoma. [19][20][21][22][23][24][25][26][27][28] In the present study, we sought to investigate the anticancer effect of RA in prostate cancer.…”
mentioning
confidence: 99%